Leprosy patients with deformities at post‐elimination stage: The Bangladesh experience. Issue 1 (14th October 2020) - Mowla, M. R.; Angkur, D. M.; Hasan, Z.; Sultana, M. N.; Afrin, S.; Akhter, M. S.
Abstract: Background: Disability assessment in leprosy patients is a very important factor in the evaluation of the effectiveness of a leprosy elimination program. Little information exists on deformities in leprosy patients in Bangladesh. Objectives: To describe the pattern and prevalence of deformities in leprosy patients after leprosy has been declared eliminated from Bangladesh in 1998. Methods: A descriptive retrospective cross‐sectional study was carried out in Chittagong Medical College Hospital using the registered records of patients for the period 2004–2013. Results: Out of 670 leprosy patients, 213 (31.79%) had deformities. The prevalence of deformity was for grade 1: 92 (43.20%), for grade 2: 121 (56.80%). Among the patients with deformity, males 144 (67.60%) outnumbered females 69 (32.40%). Four age groups were considered. The calculated age‐specific cumulative detection rates showed the highest case detection in >40 years group at 81 (38.02%). The rate of children (<14 years) was less at 7 (3.29%). Of the 213 patients with deformity, the borderline tuberculoid patients were totalled 79 (37.08%), which was higher than other forms of leprosy. Among the 121 patients with limb deformity, 57 (8.50%) had claw hand followed by wrist drop 31 (4.63%), foot drop 30 (4.48%). Three (0.45%) had a nerve abscess, 27 (4.02%) had a trophic ulcer and 7 (1.05%) patients had ocular complications. Conclusion: The grade 2 deformities among newly detected leprosy patients were still high. Claw hand was the most common deformity in the upper limbs, whereas foot drop and trophic ulcer were the most common deformities in the lower limbs. Although leprosy according to the World Health Organization has been eliminated globally, the disease continues to be a significant cause of peripheral neuropathy, deformity, disability and disfigurement in some developing countries like Bangladesh.